The Good Word Its Non-Covenant and Covenant Significance in the Old Testament - McAffee, Matthew (2015)
The Old Testament expression ‘the good word’ has long been recognized for its significance in covenant nomenclature. However, the meaning of this phrase outside of covenant contexts has not been adequately explored in the scholarly discussion. In order to provide a more nuanced explanation of its meaning and development in the Old Testament, this study analyzes ‘the good word’ according to the following two-fold categorization: (1) those instances that evince a non-covenant context for the good word, and (2) those cases that appear within the framework of covenant language. As a secondary interest, limited attention is devoted to similar phraseology in the broader ancient Near Eastern context, providing a firm basis for assessing the extra-biblical parallels that have been proposed for ‘the good word’ in the Old Testament.
Keywords: covenant promises; covenant blessings/curses; Alliance; Treaty; reliable; Favor; dabar tob; good word; Covenant